A problem by Lorenc Bushi

Level pending

Let a a , b b and c c be real numbers such that: a + b + c = 0 a+b+c=0 ,

a 2 + b 2 + c 2 = 4 a^2+b^2+c^2=4 .

Find a 4 + b 4 + c 4 = a^4+b^4+c^4= ?


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Lorenc Bushi
Jan 12, 2014

Notice that:

a 4 + b 4 + c 4 = ( a 2 + b 2 + c 2 ) 2 2 ( ( a b ) 2 + ( b c ) 2 + ( a c ) 2 ) a^4+b^4+c^4=(a^2+b^2+c^2)^2-2((ab)^2+(bc)^2+(ac)^2) .Since we already know that a 2 + b 2 + c 2 = 4 a^2+b^2+c^2=4 our problem becomes in finding the value of ( a b ) 2 + ( b c ) 2 + ( a c ) 2 (ab)^2+(bc)^2+(ac)^2 .Observe that

a 2 + b 2 + c 2 = ( a + b + c ) 2 2 ( a b + b c + a c ) = 4 a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ac)=4 .Since we know that a + b + c = 0 a+b+c=0 easily we find a b + b c + a c = 2 ab+bc+ac=-2 .But the problem is not solved yet.We must find ( a b ) 2 + ( b c ) 2 + ( a c ) 2 (ab)^2+(bc)^2+(ac)^2 .We can do the same thing to find our desired sum.

( a b + b c + a c ) 2 2 a b c ( a + b + c ) = ( a b ) 2 + ( b c ) 2 + ( a c ) 2 (ab+bc+ac)^2-2abc(a+b+c)=(ab)^2+(bc)^2+(ac)^2 .Since a + b + c = 0 a+b+c=0 the whole term that involves a b c abc is canceled and then it is not hard for us to find ( a b ) 2 + ( b c ) 2 + ( a c ) 2 = 4 (ab)^2+(bc)^2+(ac)^2=4 .Substituting this in the equation above we get our desired result which is 8 \boxed{8} .

I did it the same way the a+b+c = 0 thing is the punchline...

Eddie The Head - 7 years, 4 months ago
Prasun Biswas
Jan 17, 2014

We shall use here the identity ( a + b + c ) 2 = a 2 + b 2 + c 2 + 2 ( a b + b c + c a ) (a+b+c)^{2}=a^{2}+b^{2}+c^{2}+2(ab+bc+ca)

Given that, a + b + c = 0 a+b+c=0 ....(i) and a 2 + b 2 + c 2 = 4 a^{2}+b^{2}+c^{2}=4 .....(ii)

Squaring eq. (i), we get----

( a + b + c ) 2 = 0 2 (a+b+c)^{2}=0^{2}

( a 2 + b 2 + c 2 ) + 2 ( a b + b c + c a ) = 0 \implies (a^{2}+b^{2}+c^{2})+2(ab+bc+ca)=0

4 + 2 ( a b + b c + c a ) = 0 \implies 4+2(ab+bc+ca)=0 [From (ii)]

2 ( a b + b c + c a ) = 4 \implies 2(ab+bc+ca)=-4

a b + b c + c a = 2 \implies ab+bc+ca=-2

Squaring both sides again, we get---

( ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ) + 2 ( a b 2 c + b c 2 a + c a 2 b ) = 4 \implies ((ab)^{2}+(bc)^{2}+(ca)^{2})+2(ab^{2}c+bc^{2}a+ca^{2}b)=4

( ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ) + 2 a b c ( b + c + a ) = 4 \implies ((ab)^{2}+(bc)^{2}+(ca)^{2})+2abc(b+c+a)=4

( ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ) = 4 \implies ((ab)^{2}+(bc)^{2}+(ca)^{2})=4 [From (i)]

a 2 b 2 + b 2 c 2 + c 2 a 2 = 4 \implies a^{2}b^{2}+b^{2}c^{2}+c^{2}a^{2}=4 ......(iii)

Now, squaring eq. (ii), we get-----

( a 2 + b 2 + c 2 ) 2 = 4 2 (a^{2}+b^{2}+c^{2})^{2}=4^{2}

a 4 + b 4 + c 4 + 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) = 16 a^{4}+b^{4}+c^{4}+2(a^{2}b^{2}+b^{2}c^{2}+c^{2}a^{2})=16

a 4 + b 4 + c 4 + 2 × 4 = 16 a^{4}+b^{4}+c^{4}+2\times 4=16 [From (iii)]

a 4 + b 4 + c 4 + 8 = 16 a 4 + b 4 + c 4 = 8 a^{4}+b^{4}+c^{4}+8=16 \implies a^{4}+b^{4}+c^{4}=\boxed{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...